Do Relational Goods Raise Well-Being? An Econometric Analysis - Rasciute, S.; Downward, P.; Greene, William (2017)
Â© 2016 EEA. This paper explores the relationship between different types of relational goods and well-being and examines if there is latent/unobserved heterogeneity in this relationship by applying the latent class ordered probit model. This unique contribution to the literature examines if some individuals have a more associative disposition than others which contributes to their subjective well-being through the consumption of relational goods. As well as relational goods that have been well researched, such as marital status and household composition, this paper explores participation in sports, arts and cultural activities, as well as attendance at events or facilities for these activities, heritage visits, volunteering, and gambling.